Concise Access to α‐Arylketothioamides by Redox Reaction between Acetophenones, Elemental Sulfur and DMF. Issue 20 (11th July 2017) - Liu, Weibing; Chen, Cui; Zhou, Peng
Abstract: A copper oxide and iodine‐mediated redox reaction has been developed for the synthesis of α‐arylketothioamides from acetophenones, elemental sulfur, and N, N‐dimethylformamide (DMF). The reaction is scalable and tolerates a wide range of functional groups, providing an efficient means of accessing α‐arylketothioamides. Besides, it proceeded in an excellent step‐ and redox‐efficient manner, in which DMF and elemental sulfur both play a dual role; elemental sulfur as a nucleophilic building block and a redox moderating agent to meet the electronic requirements of the whole process, and DMF as the solvent and the surrogate of dimethylamine. Abstract : Synthesis of α‐arylketothioamides from acetophenones, elemental sulfur, and N, N‐dimethylformamide (DMF) via a copper oxide and iodine‐mediated redox reaction. The reaction is scalable and tolerates a wide range of functional groups, providing an efficient means of accessing α‐arylketothioamides.